Building Giant Carbocycles by Reversible C−C Bond Formation. (24th November 2015) - Beaudoin, Daniel; Levasseur‐Grenon, Olivier; Maris, Thierry; Wuest, James D.
Abstract: We describe a simple way to build giant macrocyclic hydrocarbons by the reversible formation of carbon–carbon bonds. Specifically, extended spirobifluorene‐substituted derivatives of Wittig's hydrocarbon were synthesized and found to undergo oligomerization, giving the largest hydrocarbon that has been crystallized and characterized by X‐ray diffraction to date.